2001
DOI: 10.1097/00006231-200110000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observation of 99mTc-thymine imaging in breast neoplasms

Abstract: New biological knowledge and new diagnostic tools for breast cancer diagnosis may have an important impact on the strategies followed by oncologists in breast cancer management. So far, it has not been possible to label a nucleotide or its precursor with technetium-99m (99mTc) for use in in vivo studies. In this paper, we report the labelling of a precursor, the nitrogenate base thymine, with 99mTc. It has been used to evaluate breast lesions. After animal studies and with the consent of patients, it was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Their results demonstrated that 18F-FMAU was selectively retained in the DNA of proliferating cells and was resistant to degradation (40). We have similarly shown that 99mTc-thymine is incorporated into cellular DNA (22). Unlike PET and PET-CT, which require expensive equipment with limited availability worldwide, conventional gamma cameras are able to perform SPECT imaging and are much more readily available.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Their results demonstrated that 18F-FMAU was selectively retained in the DNA of proliferating cells and was resistant to degradation (40). We have similarly shown that 99mTc-thymine is incorporated into cellular DNA (22). Unlike PET and PET-CT, which require expensive equipment with limited availability worldwide, conventional gamma cameras are able to perform SPECT imaging and are much more readily available.…”
Section: Discussionmentioning
confidence: 84%
“…(19,22). Here, we obtained a sensitivity of 70%, a specificity of 85.7%, an accuracy of 82.2%, and positive and negative predictive values of 58.3% and 90.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We used stannous chloride as a reducing agent in accordance with the requirements of the European Pharmacopeia. Several ratios between thymine and stannous chloride were utilized.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] We previously reported a technique for labelling the thymidine precursor thymine with 99m Tc, with good specificity and high predictive value. [16][17][18] We have also used 99m Tc-doxorubicin in dogs and cats in order to evaluate its uptake in different kinds of tumours, with promising results, which led to the approval of this pilot trial. 24 …”
mentioning
confidence: 99%